Climate refugees, refugees or under own protection? : A comparative study between climate refugees and refugees embraced by the United Nations Refugee Convention - Clarin, Malin (Fakulteten för samhälls- och livsvetenskaper, 2011)
Global warming is a current topic on the international agenda. The rise of temperature in the atmosphere threatens populations living on island, deltas and coastal areas, and people living nearby the Arctic and areas covered by permafrost are threatened. In turn this leads to the people in these areas being projected to be homeless or displaced due to climate change and the rising numbers of natural disasters. Those people are what you can label as climate refugees. According to IOM and Brown (2001) climate refugees are persons who for compelling reasons of change in the environment which change their living conditions have to escape their homes, either within their country or abroad.The United Nations Refugee Convention is the binding legislation followed by 147 (in 2008) of the UN member states. Either the UN Refugee Convention or any other international law recognizes climate refugees, and those people are due to that not granted any legal status. Who will protect these people when they have to escape their homes? This paper aims to explore what distinguish climate refugees from the refugees embraced by the UN Refugee Convention by a comparative literature review, for in this way be able to recognize the assumptions that make the United Nations to not classify climate refugees with refugee status. Both groups of refugees has in common that they live under the pressured decision they have to make as they flee their native homes to ensure their own and their families survival according to Grove (2006).In the long run both climate refugees and the UN Refugee Convention embraced refugees face the same traumatic experiences escaping their homes and have due to that the similar right to get the same mental help and be protected under international law. But populations facing the effects of global warming do not want to leave their land and believe it is an issue of human rights.